NEUROEFFECTIVE LEADERSHIP leading yourself and others. - Riddell, Patricia (ROUTLEDGE, 2025)
Viewing leadership through a neuroscientific lens is transforming the way we understand, interpret, manage, and lead ourselves and others. This book provides practical neuroscientific approaches to leadership that promote far greater effectiveness at both a personal and team level.The authors, who are experts in the fields of neuroscience and leadership, distil and combine deep neuroscience knowledge with leadership coaching tools to present clear guidance, based on years of practice, to help develop more effective leadership in organisations. Using a clear structure throughout, each key element in how to improve self-awareness and how to work effectively as a team leader is presented. Topics covered include how to develop an achieving mindset and increase resilience by reducing stress and overwhelm, how to turn rumination into action, and, at a team level, how to promote psychological safety, perceive others' realities, and create metaphors that keep teams on message.With its clarity and practical applications, this book is the perfect guide for leaders and managers wishing to improve their understanding of their own and others' behaviour. It offers guidance on how to build the skills needed to create more effective teams in the workplace. It is also a very useful tool for leadership coaches.
Keywords: Leadership -- Psychological aspects.; Neuropsychology.; elektronické knihy; electronic books